Occupational Risks during a Monkeypox Outbreak, Wisconsin, 2003 - Croft, Donita R. (Centers for Disease Control and Prevention, 2007)
We determined factors associated with occupational transmission in Wisconsin during the 2003 outbreak of prairie dog–associated monkeypox virus infections. Our investigation included active contact surveillance, exposure-related interviews, and a veterinary facility cohort study. We identified 19 confirmed, 5 probable, and 3 suspected cases. Rash, headache, sweats, and fever were reported by >80% of patients. Occupationally transmitted infections occurred in 12 veterinary staff, 2 pet store employees, and 2 animal distributors. The following were associated with illness: working directly with animal care (p = 0.002), being involved in prairie dog examination, caring for an animal within 6 feet of an ill prairie dog (p = 0.03), feeding an ill prairie dog (p = 0.002), and using an antihistamine (p = 0.04). Having never handled an ill prairie dog (p = 0.004) was protective. Veterinary staff used personal protective equipment sporadically. Our findings underscore the importance of standard veterinary infection-control guidelines.